Design And Performance Evaluation Of A Cell Loss Recovery Scheme For ATM Networks Using A Convolutional Code - Wong, Kin Yew (2001)
This thesis presents a new cell loss recovery scheme for ATM networks using an interleaved burst-error-correcting convolutional code. In particular, the proposed cell loss recovery scheme implements interleaved Berlekamp-Preparata(BP) code at the convergence sublayer(CS) of ATM adaptation layer(AAL) to compensate for cell loss.